Thermalization and quantum correlations in exactly solvable models - Cazalilla, Miguel A. (2012)
The generalized Gibbs ensemble introduced for describing few-body correlations in exactly solvable systems following a quantum quench is related to the nonergodic way in which operators sample, in the limit of infinite time after the quench, the quantum correlations present in the initial state. The nonergodicity of the correlations is thus shown analyticallyto imply the equivalence with the generalized Gibbs ensemble for quantum Ising and $XX$ spin chains as well as for the Luttinger model the thermodynamic limit, and for a broad class of initial states and correlation functions of both local and nonlocal operators.